Cognitive Orientation to (Daily) Occupational Performance intervention leads to improvements in impairments, activity and participation in children with Developmental Coordination Disorder - Thornton, A.; Licari, M.; Reid, S.; Armstrong, J.; Fallows, R.; Elliott, Catherine (Taylor and Francis Ltd, 2015)
© 2015 Informa UK Ltd. All rights reserved: reproduction in whole or part not permitted Introduction: Children diagnosed with Developmental Coordination Disorder (DCD) present with a variety of impairments in fine and gross motor function, which impact on their activity and participation in a variety of settings. This research aimed to determine if a 10-week group-based Cognitive Orientation to Daily Occupational Performance (CO-OP) intervention improved outcome measures across the impairment, activity and participation levels of the International Classification of Functioning, Disability and Health (ICF) framework. Methods: In this quasi-experimental, pre–post-test, 20 male children aged 8–10 years ((Formula presented.)9y1m?±?9?m) with a confirmed diagnosis of DCD participated in either the 10 week group intervention based on the CO-OP framework (n?=?10) or in a control period of regular activity for 10 weeks (n?=?10). Outcome measures relating to impairment (MABC-2, motor overflow assessment), activity (Handwriting Speed Test) and participation [Canadian Occupational Performance Measure, (COPM) and Goal Attainment Scale) were measured at weeks 0 and 10 in the intervention group. Results: Children who participated in the CO-OP intervention displayed improvements in outcome measures for impairment, activity and participation, particularly a reduction in severity of motor overflow. Parent and child performance and satisfaction ratings on the COPM improved from baseline to week 10 and all goals were achieved at or above the expected outcome. No significant changes were reported for the control group in impairment and activity (participation was not measured for this group). Conclusion: The strategies implemented by children in the CO-OP treatment group, targeted towards individualised goal attainment, show that CO-OP, when run in a group environment, can lead to improvements across all levels of the ICF.Implications for RehabilitationDevelopment Coordination Disorder is a condition which has significant physical, academic and social impacts on a child and can lead to activity limitations and participation restrictions.Cognitive Orientation to Daily Occupational Performance is an approach which uses cognitive-based strategies to improve performance of specific tasks based on child chosen goals.The intervention program had a positive effect on self-perceived levels of performance which may lead to changes in quality of life.Parents felt the intervention enhanced socialisation, peer modelling and encouragement and felt that this increased confidence and independence.